2020
DOI: 10.1002/anie.202011022
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystal Red Phosphors and Their Core–Shell Structure for Improved Water‐Resistance for Laser Diodes Applications

Abstract: A solvent‐vapor transport route produces centimeter‐sized single‐crystal red phosphors. The epitaxial growth route to yield its core–shell structure at ambient temperature was adopted. These red phosphors could be applied in all‐inorganic WLED devices. Cs2TiF6:Mn4+ (CTFM) single crystal provides enhancement of quantum efficiency, moisture resistance, and thermal stability compared to polycrystalline powders. The internal quantum efficiency can reach as high as 98.7 %. To further improve waterproof stability, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…K 2 SiF 6 has slightly larger water solubility than BaTiF 6 , but the difference is limited. Several recent studies , reported that the single-crystal phosphors possess higher moisture resistance than their corresponding polycrystalline powdery form. It is thus deduced that the single-crystal nature of the BaTiF 6 :Mn 4+ with the relatively big size is also responsible for the improvement of water resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…K 2 SiF 6 has slightly larger water solubility than BaTiF 6 , but the difference is limited. Several recent studies , reported that the single-crystal phosphors possess higher moisture resistance than their corresponding polycrystalline powdery form. It is thus deduced that the single-crystal nature of the BaTiF 6 :Mn 4+ with the relatively big size is also responsible for the improvement of water resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Many strategies have been proposed to prevent the [MnF 6 ] 2– group from hydrolysis. We have classified them into the following six classes, (1) coating with a hydrophobic organic compound, (2) coating with an inorganic layer, (3) self-coating to form a core–shell structure, (4) reductive treating to form Mn 4+ -rare surface passivation, (5) recrystallization by hydrothermal treatment, and (6) preparation of bulk single-crystal phosphor. For the last strategy, our study demonstrates that the Na 2 SiF 6 :Mn 4+ single crystals indeed experience a much slower hydrolysis-induced deterioration than its polycrystalline powdery form. Furthermore, we recently compared the deterioration behavior of BaSiF 6 :Mn 4+ , Na 2 SiF 6 :Mn 4+ , and (NH 4 ) 2 SiF 6 :Mn 4+ phosphors in water and further find that the deterioration rate is closely related to their specific solubility.…”
Section: Introductionmentioning
confidence: 98%
“…[ 7 ] In present, most of Mn 4+ ‐doped fluoride phosphors, in the form of A 2 B F 6 :Mn 4+ or A 3 M F 6 :Mn 4+ ( A = alkali metal cations; B = Si 4+ , Ge 4+ , Ti 4+ , Zr 4+ ; M = Al 3+ , Ga 3+ , Sc 3+ ), possess high internal QEs (IQEs, >80%). [ 4,8–10 ] However, on account of the above transition characteristic, all the phosphor absorption efficiency (AEs) remains low and hence a relatively poor external quantum efficiency (EQEs, <40%). [ 11–13 ] There are practical implications in increasing the Mn 4+ doping concentration for enhanced absorption whilst maintaining high IQE at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Note: the yellow colored part is the Cs 2 TiF 6 :Mn 4+ core and colorless part is the Cs 2 TiF 6 shell. 36 These studies demonstrate that the single crystal fluoride phosphors show superior water resistance property than the powder phosphor, and high-quality bulk ingot can be readily prepared at facile conditions due to the ionic bonding nature of fluorides. Besides, a Mn 4+ -free shell can also be grown on the Mn 4+ -doped single crystals for further shielding.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 82%
“…Fig. 14 Photographs of Cs 2 TiF 6 :Mn 4+ single crystal, silicone, and Y 3 Al 5 O 12 :Ce 3+ (YAG:Ce) crystal after heat treatment at 150 °C during the different aging periods 36. …”
mentioning
confidence: 99%